Researches on defect localization based on discrete ellipse imaging algorithm for curved plates. (August 2019) - Zhai, Shuangmiao; Zhou, Shaoping; Chen, Shaojie
Abstract: Discrete ellipse imaging algorithm based on Lamb waves is widely applied in defect detection for plate-like structures. In this paper, the effectiveness of discrete ellipse imaging algorithm for the defect detection in curved plates has been investigated experimentally. The experiment with different sensor arrays and different numbers of sensors has been conducted. Experimental results show that the sparse array has a better imaging accuracy and the imaging accuracy improves as the number of sensor increases. The localization results show that the location of defect cannot been confirmed accurately. To improve the imaging accuracy, a novel method based on zero-signal filling is proposed in this paper. The experimental results show that the novel method can improve the imaging accuracy in curved plates effectively. Highlights: Propagation characteristics of Lamb wave in the curved plates have been investigated. S0 mode and 300 kHz are selected as the exciting mode and frequency in the experiment. The sparse array has a better imaging accuracy and the imaging accuracy improves as the number of sensor increases. The method of zero-signal filling is proposed to improve the imaging accuracy of defect inspection.